ADAMTS-13 regulates platelet adhesion under flow - Shenkman, Boris; Budde, Ulrich; Angerhaus, Dorothea; Lubetsky, Aharon; Savion, Naphtali; Seligsohn, Uri; Varon, David (Thrombosis and Haemostasis, 2006)
ADAMTS-13 cleaves large and ultra-large vonWillebrand factor multimers normally secreted by endothelial cells. Severe deficiency of this enzyme leads to thrombotic thrombocytopenic purpura (TTP). We applied the Impact-R system [Cone and plate(let) Analyzer, CPA] to determine optimal conditions for ADAMTS-13 function, to assess it’s activity in TTP patients and to distinguish inheritedTTP (inTTP) from acquiredTTP (acTTP). The role of ADAMTS-13 in platelet adhesion under different conditions was investigated applying recombinant forms of VWF and ADAMTS-13. rVWF was first treated by rADAMTS-13 either in solution or when immobilized on the surface of the well, under static or flow conditions, in the presence or absence of BaCl2. The resulting cleavedVWF fragments were then immobilized and served to assess type 3 von Willebrand disease whole blood platelet adhesion under flow. Maximal effect of the rADAMTS-13 (decrease of platelet adhesion in the absence compared to the presence of BaCl2), was observed when the rVWF was pre-immobilized and the cleavage step took place under flow (85%). Mixing plasma ofTTP patients with normal blood (1:3) yielded a 1.6 to 2-fold increase of platelet adhesion under flow compared to mixing normal plasma with normal blood, at shear rate range of 1,800–2,500s−1. Maximal increase of platelet adhesion was observed under 2,050s−1. Under these conditions, the extent of adhesion was similarly higher in patients with inTTP and acTTP versus control [surface coverage (SC) 14.5 ± 2.8% and 14.6 ± 2.5% vs. 7.4 ± 1.7%, respectively]. ADAMTS-13 activity measured by collagen-binding test was similarly low (4.2 ± 3.8% and 3.5 ± 2.4% vs. 72.2 ± 8.0%, respectively). An inverse correlation between SC and ADAMTS-13 activity was observed in a patient with inTTP assayed eight times during plasma infusion treatment. Addition of BaCl2 to the mixture of TTP plasma and normal whole blood yieldeda decrease in platelet adhesion in inTTP (by 51%) but not in acTTP. The lack of reduction of platelet adhesion in acTTP could presumably be due to the presence of ADAMTS-13 inhibitor in these patients. These results suggest that VWF immobilization and high shear flow yielded optimal conditions for ADAMTS-13 activity, and that introduction of BaCl2 in the Impact-R (CPA) test may be useful for differentiation between inherited and acquired TTP.
Keywords: ADAMTS-13; TTP; VWF; Impact-R